Determinants of voter turnout in 2015 Tanzania general election: a case of morogoro municipality, Tanzania - Muhanga, Mikidadi (SPC Journal of Social Sciences, 2018)
Worldwide votersâ€™ turnout shows a notable decline since the mid 1980s, this is a challenge to democratization process. A number of efforts have been in place to address this, still a great proportion of registered voters do not vote in the elections as revealed in 1995, 2000, 2005 and 2010 General elections in Tanzania. This study was designed to assess the context specific determinants of votersâ€™ turnouts in Tanzania general election in Morogoro municipality after all the efforts by various stakeholders to address low turn outs experienced in earlier elections. Specifically the study determined votersâ€™ turnouts and analyzed motives for voting. A cross- sectional study design was employed. Questionnaire was used as a tool for data collection to gather both qualitative and quantitative information. Multistage sampling was employed. Data were collected from four randomly selected wards from Morogoro urban (purposively selected) in Morogoro region namely Kichangani, Tungi, Mazimbu and Mji Mpya where in each ward 60 individuals were drawn randomly. Data processing and analysis was done using Statistical Package for Social Sciences (SPSS) computer software. Chi-square test indicates significant associations between marital status and voting (p = 0 .000), voters education and the likelihood of voting (p = 0.000) and access to information and the likelihood of voting (p = 0 .001). The motives for turning to vote in general election in the study area were leadership role towards development (22.5%), exercising democracy (17.5%), good policies of political parties and manifestos (20.0%) and achievement done by former leaders (15.0%), good promises made by candidates during campaigns (10.0%) and voted to avoid corrupt leaders (15.0%). The study recommends for provision of civic education programme to citizens through various means and rigorous campaigns to disclose candidatesâ€™ potentialities.Â Â